Business Process ManagementWorkshops BPM 2010 InternationalWorkshops and Education Track Hoboken, NJ, USA, September 1315, 2010 Revised Selected Papers - Muehlen, Michael zur (Springer, 2012)
This book constitutes the thoroughly refereed post-workshop proceedings of nine international workshops held in Hoboken, NJ, USA, in conjunction with the 8th International Conference on Business Process Management, BPM 2010, in September 2010.